Dear teacher : 100 days of inspirational quotes and anecdotes - Johnson, Brad, 1969-; Bowman, Hal (New York, NY : Routledge, 2021)
'Dear teachers, you are appreciated! This inspirational book, written by motivational speakers Brad Johnson and Hal Bowman, provides daily encouragement to thank you for all that you do in the classroom and beyond. Johnson and Bowman offer quotes and powerful stories for 100 days of the school year, highlighting topics such as celebrating small successes, bringing out the best in your students, knowing your worth, and being all in. The book is perfect for teachers of all grade levels, and for principals to buy their teachers for schoolwide morale, to keep teachers feeling their best. The uplifting advice will remind you why you've chosen this profession and the impact you have on others!'--
Meet the Authors; Preface; 100 Days of Inspirational Quotes and Anecdotes
OCLC-licensed vendor bibliographic record.
Keywords: Teachers -- Conduct of life; Motivation in education; EDUCATION / Professional Development; EDUCATION / Philosophy & Social Aspects